Calibration and imaging with variable radio sources - Mbou Sob, Ulrich Armel (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2017)
Calibration of radio interferometric data is one of the most important steps that are required to produce high dynamic range radio maps with high fidelity. However, naive calibration (inaccurate knowledge of the sky and instruments) leads to the formation of calibration artefacts: the generation of spurious sources and the deformations in the structure of extended sources. A particular class of calibration artefacts, called ghost sources, which results from calibration with incomplete sky models has been extensively studied by Grobler et al. (2014, 2016) and Wijnholds et al. (2016). They developed a framework which can be used to predict the fluxes and positions of ghost sources. This work uses the approach initiated by these authors to study the calibration artefacts and ghost sources that are produced when variable sources are not considered in sky models during calibration. This work investigates both long-term and short-term variability and uses the root mean square (rms) and power spectrum as metrics to evaluate the "quality" of the residual visibilities obtained through calibration. We show that the overestimation and underestimation of source flux density during calibration produces similar but symmetrically opposite results. We show that calibration artefacts from sky model errors are not normally distributed. This prevents them from being removed by employing advanced techniques, such as stacking. The power spectrums measured from the residuals with a variable source was significantly higher than those from residuals without a variable source. This implies advanced calibration techniques and sky model completeness will be required for studies such as probing the Epoch of Reoinization, where we seek to detect faint signals below thermal noise.
Keywords: Uncatalogued